(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
In the field of health care, patient autonomy is a critical problem. It is common knowledge that patients’ understanding of legal and ethical problems surrounding the consent procedure is poor. As a result, the purpose of this study was to determine patient understanding, attitude, and views of the legal nature of informed consent. From